2019
DOI: 10.1158/1940-6207.capr-18-0284
|View full text |Cite
|
Sign up to set email alerts
|

Case-only Methods Identified Genetic Loci Predicting a Subgroup of Men with Reduced Risk of High-grade Prostate Cancer by Finasteride

Abstract: In the Prostate Cancer Prevention Trial (PCPT), genotypes that may modify the effect of finasteride on the risk of prostate cancer have not been identified. Germline genetic data from 1,157 prostate cancer cases in PCPT were analyzed by case-only methods. Genotypes included 357 SNPs from 83 candidate genes in androgen metabolism, inflammation, circadian rhythm, and other pathways. Univariate case-only analysis was conducted to evaluate whether individual SNPs modified the finasteride effect on the risk of high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…[2][3][4] Finasteride have three crystal structures and six solvates, [5][6][7][8] while form I is pharmaceutically preferred due to its better stability. 7,9 The present study showed that finasteride has new pharmacodynamic activities in polycystic ovary syndrome (PCOS) therapy and the ability of reducing the risk of bladder cancer and high-grade prostate cancer, [10][11][12] which could demonstrate the great research value of finasteride.…”
Section: Introductionmentioning
confidence: 64%
“…[2][3][4] Finasteride have three crystal structures and six solvates, [5][6][7][8] while form I is pharmaceutically preferred due to its better stability. 7,9 The present study showed that finasteride has new pharmacodynamic activities in polycystic ovary syndrome (PCOS) therapy and the ability of reducing the risk of bladder cancer and high-grade prostate cancer, [10][11][12] which could demonstrate the great research value of finasteride.…”
Section: Introductionmentioning
confidence: 64%